PENANGANAN GAGAL JANTUNG DIASTOLIK - Rampengan, Starry H (UNIVERSITAS SAM RATULANGI, 2013)
Abstract: Diastolic heart failure (HF) is also referred to as heart failure with normal left ventricular systolic function (normal ejection fraction). The difference between the systolic and diastolic HFs is based on their pathophysiology. In the diastolic HFs, the left ventricular function is normal or slightly impaired. The typical manifestations have an increased filling pressure caused by impaired relaxation and compliance of the left ventricle. The management of diastolic HFs includes antihypertensive treatment, maintenance of the sinus rhythm, prevention of tachycardia, reduction of venous pressure, prevention of myocardial ischemia, and prevention of diabetes mellitus. The aim of the diastolic HFs is: to reduce the progression, to relieve its symptoms, to eliminate exacerbations, and to reduce the mortality. The predisposing factors for the diastolic dysfunction include elderly age, female sex, obesity, coronary artery disease, hypertension, and diabetes mellitus. The European Society of Cardiology specifies therapy in diastolic HFs based on: angiotensin converting enzyme inhibitors, angiotensin receptor blockers, beta-blockers, non-dihydropyridine calcium channel blockers, and diuretics. Keywords: diastolic heart failure, management. Abstrak: Gagal jantung diastolik disebut juga sebagai gagal jantung dengan fungsi sistolik ventrikel kiri yang normal (fraksi ejeksi normal). Perbedaan antara gagal jantung sistolik dan diastolik terletak pada patofisiologinya. Pada gagal jantung diastolik fungsi ventrikel kiri normal atau sedikit menurun. Manifestasi yang timbul disebabkan oleh peningkatan tekanan pengisian yang diakibatkan oleh gangguan relaksasi dan komplains ventrikel kiri. Manajemen gagal jantung diastolik meliputi terapi antihipertensi, pemeliharaan irama sinus, pencegahan takikardi, pengurangan tekanan vena, pencegahan iskemik miokard dan pencegahan diabetes melitus. Tujuan terapi gagal jantung diastolik yaitu mengurangi progresivitas, menghilangkan gejala, mencegah eksaserbasi dan menurunkan angka mortalitas. Faktor predisposisi disfungsi diastolik meliputi usia lanjut, jenis kelamin wanita, obesitas, penyakit jantung koroner, hipertensi, dan diabetes melitus. The European Society of Cardiology mengeluarkan beberapa macam penatalaksanaan gagal jantung diastolik berdasarkan: ACE-inhibitors, angiotensin receptor blocker, beta blocker, non dihydropiridine calcium channel blocker, dan diuretik. Kata kunci: gagal jantung diastolik, penatalaksanaan.